Pemecahan Sertifikat Hak atas Tanah yang Masih Dibebani Hak Tanggungan - Ahmad Habibie Rachman (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to identify and analyze the process of dividing land ownership certificates that are still encumbered by mortgage rights. The research questions focus on two main issues: first, the legal consequences of dividing land rights on properties still under mortgage; second, the legal protection provided to banks as creditors regarding such division.The research method employed is a combination of normative and empirical legal approaches. The normative approach involves examining relevant legislation, while the empirical approach includes interviews to support the findings of the normative analysis. The findings indicate that dividing the land ownership certificate still encumbered by mortgage rights will result in the nullification of the mortgage attached to the original certificate. Such division can only be executed after obtaining written consent from the mortgage holder or authorized parties to remove the respective encumbrance. Furthermore, records of mortgage rights and other encumbrances listed in the land registry and the original certificate must be re-recorded in the new land registry and certificate. Legal protection for creditors, particularly banks, against the division of land ownership certificates still encumbered by mortgage rights involves several steps. These include issuing a power of attorney to encumber mortgage rights before the division to protect loans extended to debtors. Additionally, a power of attorney to sell is necessary to ensure certainty in the sale of the encumbered asset.